Métodos alternativos ao uso do “Tea Bag Index” (TBI) para aprimorar a avaliação da decomposição da matéria orgânica em solo de manguezal na zona semiárida do Brasil - Vasquez, Tamia Daniela Cabascango (2024)
Mangroves are highly relevant coastal ecosystems, regarded as some of the most productive on the planet. Their high primary productivity and the anaerobic conditions of their soils result in less efficient decomposition of organic matter (OM), thereby enabling significant carbon (C) storage. Consequently, mangroves play a crucial role in biodiversity conservation and in strategies for mitigating and adapting to climate change. However, these ecosystems face substantial anthropogenic impacts, such as shrimp farming, particularly along the northern and northeastern coasts of Brazil. These impacts lead to deforestation, contamination by potentially toxic elements, eutrophication, and alterations in biogeochemical processes that affect carbon retention. Standardized methods such as the Tea Bag Index (TBI) assess OM decomposition in soils, allowing for the measurement and comparison of decomposition rates using commercial tea bags across different sites. Nevertheless, the use of alternative materials, such as leaves from mangrove species and locally available organic materials like yerba mate, could enhance the method's applicability and broaden understanding of decomposition processes.This study aimed to refine the TBI method by employing different organic materials and experimental fabrics. Decomposition experiments were conducted in a mangrove ecosystem in the Pacoti River, utilizing 12 experimental treatments. These included bags with standard green tea, Lipton® commercial green tea, leaves of Rhizophora mangle and Avicennia germinans, yerba mate, and different fabrics (perlon and escaline). The results indicated that Sencha green tea and mangrove leaves exhibited decomposition rates similar to the TBI standard, suggesting their potential as substitutes. Moreover, perlon fabric demonstrated superior efficiency, achieving up to 8% higher OM decomposition. The study also compared decomposition processes in preserved mangrove soils with those impacted by shrimp farming effluents in the Acaraú River, Ceará state. Soil characterization (Eh, pH, granulometry, and pyritization degree) provided complementary information about the biogeochemical environment of these areas. In shrimp farming-impacted areas, a higher OM decomposition percentage (79%) was observed with perlon fabric, accompanied by elevated nutrient contents from effluents, such as phosphorus (25.3 mg kg−1), and a significantly lower pyritization degree (6%) compared to non-impacted areas (15%). These findings suggest a reduced carbon storage capacity in impacted soils. These results are critical for understanding how anthropogenic impacts alter decomposition processes and for improving conservation methods that promote carbon sequestration and storage.